Exosome therapy from hypoxia-preconditioned mesenchymal stem cell exosomes: Anti-inflammatory and wound closure effects in third-degree burns : - Soemitha, Christiani Natalia; Setiawan, Eko; Chodidjah, Chodidjah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Background: Third-degree burns cause extensive tissue damage, prolonged inflammation, and delayed wound healing. Increased expression of pro-inflammatory cytokines, particularly interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), may worsen tissue injury and impair repair. Modulating these mediators may improve healing outcomes in third-degree burns.Objective: To evaluate the effect of hypoxia-conditioned mesenchymal stem cell exosomes (HC-MSC-Exo) on IL-1β and TNF-α mRNA expression in a model of third-degree burns.Methods: An experimental post-test-only for control s study was conducted using thirty male Wistar rats (6–8 weeks; 200–250 g). Animals were randomly divided into five grups study: healthy control, burn + NaCl, burn + silver sulfadiazine, burn + HC-MSC-Exo 100 μg/mL, and burn + HC-MSC-Exo 200 μg/mL. Third-degree burns were induced using a 2 × 2 cm2 heated copper plate. The HC-MSC-Exo was administered subcutaneously around the wound. Wound evaluation was performed on days 0, 3, and 7. On day 7, burn tissue was collected for analysis of IL-1β and TNF-α mRNA expression.Results: Untreated burn wounds showed higher IL-1β and TNF-α mRNA expression than healthy controls. HC-MSC-Exo administration reduces the expression of both inflammatory markers, with the 200 μg/mL group showing the lowest levels. Macroscopic wound healing also improves in the HC-MSC-Exo, particularly in the 200 μg/mL , as indicated by smaller wound area and less visible necrotic tissue.Conclusion: HC-MSC-Exo reduces IL-1β and TNF-α mRNA expression and improves macroscopic wound healing in a model of third-degree burns, suggesting that HC-MSC-Exo may be a promising therapeutic approach for burn injury.